Elderly participation in music and art activities: satisfaction assessment - SOONTORNTANAPHOL, N. (Utopía y Praxis Latinoamericana, 2021)
ABSTRACT The objective of this research is to assess satisfaction with the participation in music and art activities of the elderly. The research results revealed that the satisfaction on participation in music and overall arts activities was at the highest level due decision-making, of the elderly people on what they wanted or liked. In practice, the elderly participated in music and art activities by joining in the thinking, planning, acting, and solving problems process. Regarding the benefits, the elderly benefited both physically and mentally. In the assessment, the elderly participated in self-assessment and satisfaction with music and art activities. RESUMEN El objetivo de esta investigación es evaluar la satisfacción sobre la participación en actividades musicales y artísticas de las personas mayores. Los resultados de la investigación revelaron que la satisfacción de dichas actividades en general estaba en el nivel más alto debido a que las personas mayores toman decisiones sobre lo que quieren o les gusta. En la práctica, los ancianos participaron en actividades de música y arte al unirse al proceso de pensamiento, planificación, actuación y resolución de problemas. En cuanto a los beneficios, los ancianos se beneficiaron tanto física como mentalmente. En la evaluación, los adultos mayores participaron en la autoevaluación de su satisfacción en las actividades musicales y artísticas.